2016
DOI: 10.1080/14767058.2016.1261400
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine combined with sedative/anesthetic drugs triggers widespread neuroapoptosis in a mouse model of prematurity

Abstract: Objectives Caffeine (CAF) and sedative/anesthetic drugs (SADs) are often coadministered to premature infants in the neonatal intensive care unit (NICU). While SAD neurotoxicity in the developing brain is well established, it is not fully clear whether CAF interacts with SADs and whether this interaction is detrimental. Using a mouse model of prematurity, we hypothesized that CAF would increase apoptotic neurotoxicity when coadministered with SADs. Methods Postnatal day 3 mice were treated with vehicle or 80 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…It has been shown that caffeine treatment (10 to 80 mg/kg, i.p.) activated apoptosis (CASP3, AIF) and increased TUNEL staining in the brain of rat pups (P3, P6) ( Table 9) (Cabrera et al, 2017;Endesfelder et al, 2017a,b). Recently, Noguchi and colleagues showed that caffeine treatment in fetal macaque (110-120 days GA) anesthetized with isoflurane strongly sensitized brain (CX, ST, and CB) against isoflurane-induced apoptosis, especially NeuN-positive neurons, more than MBP-positive oligodendrocytes (Noguchi et al, 2018).…”
Section: Caffeinementioning
confidence: 97%
“…It has been shown that caffeine treatment (10 to 80 mg/kg, i.p.) activated apoptosis (CASP3, AIF) and increased TUNEL staining in the brain of rat pups (P3, P6) ( Table 9) (Cabrera et al, 2017;Endesfelder et al, 2017a,b). Recently, Noguchi and colleagues showed that caffeine treatment in fetal macaque (110-120 days GA) anesthetized with isoflurane strongly sensitized brain (CX, ST, and CB) against isoflurane-induced apoptosis, especially NeuN-positive neurons, more than MBP-positive oligodendrocytes (Noguchi et al, 2018).…”
Section: Caffeinementioning
confidence: 97%
“…This neuroprotection may also been seen in later behavioral testing (Kumral et al, ). However, this literature remains controversial, as other studies have found that caffeine at high doses may actually augment apoptosis, rendering caffeine as a drug that augments neurotoxicity that already occurs with anesthetic drug exposure (Cabrera et al, ). A recent review suggests that there is an urgent need to better understand the effects of caffeine on the developing brain using clinically relevant animal models so that the maximal safe dose for a preterm brain can be determined (Atik et al, ).…”
Section: Insights From Animal Studies: What Is the Evidence For Neuromentioning
confidence: 99%
“…The only available evidence is from a study showing that caffeine reverses the effects of general anaesthesia [20]. On the other hand, there is enough data in the literature showing that caffeine may interact unfavorably with sedative/anesthetic drugs to trigger a particularly aggressive apoptotic response in the infant's brain [21].…”
Section: Discussionmentioning
confidence: 99%
“…Another study that may support this argument was a Cochrane review showing that caffeine, when used as an adjuvant (along with analgesics like paracetamol and ibuprofen), had a small but statistically significant benefit at doses of 100 mg or more [27]. The other supporting evidence is from studies in premature infants showing that caffeine may augment the neurotoxic action of anesthetic medication indicated for neonatal sedation/anesthesia in the neonatal intensive care unit (NICU) by triggering widespread apoptosis in the developing brains of premature infants [21].…”
Section: Discussionmentioning
confidence: 99%